C3 segmental vertebral artery and its surgical implication in craniovertebral junction anomalies: Insights from two cases - Das, Kuntal Kanti (J Craniovertebr Junction Spine, 2021)
A spectrum of vertebral artery (VA) anomalies have been described with or without an associated congenital craniovertebral junction (CVJ) anomalies. C3 segmental VA, where the VA enters the dura at the level of C2/3 intervertebral foramen is an extremely rare anomaly. We report two cases of congenital CVJ anomaly (irreducible in one with C2/3 fusion and reducible in the other; without any subaxial fusion but with articular agenesis at C2/3 joint on the anomalous artery side). Computed tomographic angiography revealed intraspinal intradural entry of VA through the C2/3 intervertebral foramen on the right side with the contralateral artery found crossing the atlanto-axial joint. Both the patients underwent posterior approach and C2 was spared from instrumentation in both cases. Postoperatively, the patient with irreducible dislocation recovered well while the patient with reducible dislocation expired, possibly secondary to the thrombosis of the dominant VA from C2/3 foraminal encroachment. C3 segmental VA may be advantageous in aggressively exposing the C1/2 joint but instrumentation of C2 or C3 needs caution in view of the possibility of VA injury. Our experience shows that VA may be endangered even while exposing and protecting the artery. For such cases, we recommend posterior decompression of the C2/3 neural foramen during instrumentation in the absence of associated C2/3 fusion, as an abnormal joint morphology of C2/3 indicates a C2/3 instability.